2015
DOI: 10.1094/phyto-07-14-0185-r
|View full text |Cite
|
Sign up to set email alerts
|

Host Genotype and Hypersensitive Reaction Influence Population Levels of Xanthomonas campestris pv. vitians in Lettuce

Abstract: Dynamics of population sizes of Xanthomonas campestris pv. vitians inoculated onto or into lettuce leaves were monitored on susceptible and resistant cultivars. In general, population growth was greater for susceptible (Clemente, Salinas 88, Vista Verde) than resistant (Batavia Reine des Glaces, Iceberg, Little Gem) cultivars. When spray-inoculated or infiltrated, population levels of X. campestris pv. vitians were consistently significantly lower on Little Gem than on susceptible cultivars, while differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Investigation into Xhv strain diversity has been vital to the development and application of effective strategies for the management of BLS. In 2015, Bull et al (2015) demonstrated that some, but not all, of the 120 Xhv strains evaluated resulted in a hypersensitive response (HR) to limit the spread of infection upon inoculation into Lactuca sativa cvs. Little Gem, Pavane, and La Brillante, and that these strains did not cause HR in the other lettuce cultivars that were tested.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation into Xhv strain diversity has been vital to the development and application of effective strategies for the management of BLS. In 2015, Bull et al (2015) demonstrated that some, but not all, of the 120 Xhv strains evaluated resulted in a hypersensitive response (HR) to limit the spread of infection upon inoculation into Lactuca sativa cvs. Little Gem, Pavane, and La Brillante, and that these strains did not cause HR in the other lettuce cultivars that were tested.…”
Section: Introductionmentioning
confidence: 99%
“…The variations in host responses to phytoplasma infection may be attributed to differences in physiology, genetics, and defense mechanisms of these two plant species. The variation in pathogen load across different plant hosts is a well-established phenomenon [ 35 , 36 , 37 , 38 , 39 ]; for instance, the population sizes of Xanthomonas campestris pv. vitians change in lettuce with different genotypes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variation in pathogen load across different plant hosts is a well-established phenomenon [ 35 , 36 , 37 , 38 , 39 ]; for instance, the population sizes of Xanthomonas campestris pv. vitians change in lettuce with different genotypes [ 36 ]. Another example is the differing susceptibility of grapevine varieties to Plasmopara viticola , the causal agent of downy mildew, where specific grapevine cultivars support higher pathogen loads due to genetic differences in disease resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lettuce cultivars used in this study were previously characterized for their resistance to BLS by Nicolas et al (2018; Table 1), according to a modified version of the method developed by Bull et al (2015). Cultivars were classified into three groups based on their susceptibility to BLS: tolerant group with Batavia Reine des Glaces (BRG), Little Gem (LIG), Estival (EST) and Hochelaga (HOC); intermediate group with Romora (ROM) and Turbo (TUR); and susceptible group with Chief (CHI), Gorilla (GOR), Paris Island Cos (PIC) and Vista Verde (VIV).…”
Section: Methodsmentioning
confidence: 99%
“…The current phytosanitary products used to control BLS have to date shown poor efficiency (Lu and Raid, 2013). Common control strategies such as prophylactic measures, specifically removal of crop debris and use of clean farm machinery, are often ineffective because occurrence of this disease is sporadic (Bull et al, 2015). Nevertheless, the most widely accepted strategy for controlling BLS of lettuce is the use of resistant cultivars (Bull and Koike, 2005).…”
Section: Introductionmentioning
confidence: 99%